Poverty Conditions and Policy Solutions in Banten Province (Data Analysis Years 2009-2013) - Muhammad Findi; Veni Lutfiani Zulia (AFEBI Economic and Finance Review, 2016)
The aim of this study is to describe conditions of regional poverty to analyze the factors that affect the level of poverty in Banten province from 2009 to 2013, and to formulate solutions minimizing problems of poverty in the province of Banten. A methods used in this study is regression using panel data. Variables in this study are economic growth, minimum wage, unemployment, and literacy rate. The result of this study show that that significant variables on poverty levels in province of Banten are minimum wage, unemployment, and literacy rate. While variable is not significant to level of poverty in province of Banten is economic growth.JEL Classification: I30, J30, N30Keywords: Banten Province, Poverty, Regression Panel Data